The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11356-015-5531-2
|View full text |Cite|
|
Sign up to set email alerts
|

Quantitatively evaluating detoxification of the hepatotoxic microcystin-LR through the glutathione (GSH) pathway in SD rats

Abstract: Glutathione (GSH) plays crucial roles in antioxidant defense and detoxification metabolism of microcystin-LR (MC-LR). However, the detoxification process of MC-LR in mammals remains largely unknown. This paper, for the first time, quantitatively analyzes MC-LR and its GSH pathway metabolites (MC-LR-GSH and MC-LR-Cys) in the liver of Sprague-Dawley (SD) rat after MC-LR exposure. Rats received intraperitoneal (i.p.) injection of 0.25 and 0.5 lethal dose 50 (LD 50 ) of MC-LR with or without pretreatment of buthio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“… Figure 3 showed MC-GSHs had lower toxicity than their native toxins in the sequence of MCLR (IC 50 = 2.5  μ g/L) > MCRR (IC 50 = 24.4  μ g/L) > MCLR-GSH (IC 50 = 86.6  μ g/L) > MCRR-GSH (IC 50 = 98.7  μ g/L). Similar to previous studies [17, 21], it was not difficult to find that GSH conjugation was an effective way to control the toxicity of MCs. Though the toxicity of MC-GSHs was obviously decreased, the secondary biotoxicity of MC-GSHs was real and nonnegligible.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“… Figure 3 showed MC-GSHs had lower toxicity than their native toxins in the sequence of MCLR (IC 50 = 2.5  μ g/L) > MCRR (IC 50 = 24.4  μ g/L) > MCLR-GSH (IC 50 = 86.6  μ g/L) > MCRR-GSH (IC 50 = 98.7  μ g/L). Similar to previous studies [17, 21], it was not difficult to find that GSH conjugation was an effective way to control the toxicity of MCs. Though the toxicity of MC-GSHs was obviously decreased, the secondary biotoxicity of MC-GSHs was real and nonnegligible.…”
Section: Resultssupporting
confidence: 77%
“…However, they had lower intensities than the newly formed ions with MS signals at m/z 1302.8792 and 673.4521/1345.8864. As GSH was about 307.3235 Da, the above MS signals should be attributed to the addition products of GSH to MCLR or MCRR [21]. In addition, a product with MS signal at m/z 613.6493 was also found in both addition samples.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the pathways include Glutathione metabolic pathway, AKT signaling, EGFR signaling, response to hypoxia and oxidative stress, Cell cycle regulation, etc. are known to play a critical role in antioxidant defense, detoxification mechanisms, cell survival, proliferation, oncogenesis and NSCLC progression (Wagner and Schmidt, 2011 ; Guo et al, 2015 ). Further, the deregulation of many signaling pathways such as EGF/RAS/RAF/MEK/ERK and PI3K/AKT/mTOR is considered to play a critical role in oncogenesis and cancer progression (Memmott and Dennis, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…GSH also conjugates with electrophiles and thus participates in the metabolism and detoxification of endogenous compounds and xenobiotic toxicants, as a major detoxification agent in cells. It has been shown that MCs bind to GSH, forming conjugates (MC-GSH) via glutathione S-transferase (GST), as the first step in the detoxification process, followed by degradation to the cysteine conjugates (MC-Cys) [70,71]. The conjugation makes the toxin more soluble in water, supporting the excretion of toxin from the cells and organisms.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…The initial depletion of GSH and subsequent induction of GSH de novo synthesis might suggest a key role of GSH in the detoxification of MC-LR and protection against oxidative stress [55]. There's also evidence that pretreatment of buthionine-(S,R)-sulfoximine (BSO), a specific GSH synthesis inhibitor, significantly reduced the detoxification of MC-LR and enhanced the level of oxidative stress and hepatotoxicity in SD rats [55,64,71].…”
Section: Oxidative Stressmentioning
confidence: 99%